Calcination system-induced nanocasting synthesis of uniform Co3O4 nanoparticles with high surface area and enhanced catalytic performance. Issue 45 (20th May 2015) - Sun, Xiaohong; You, Rui; Hu, Xudong; Mo, Junbin; Xiong, Rui; Ji, Huiming; Li, Xiaolei; Cai, Shu; Zheng, Chunming; Meng, Ming
<x xml:space="preserve">Abstract</x> Nanoscale Co3O4 synthesized by open-system nanocasting with uniform size, high surface area, large pore-distribution and abundant active-sites exhibited improved catalysis.